Metode Altman Z-Score Untuk Memprediksi Kebangkrutan Perusahaan Manufaktur Di Kota Batam - Hikmah Hikmah; Sri Afridola (LPPM Universitas Putera Batam, 2018)
Manufacturing companies in Batam City experienced many bankruptcy of oil and gas companies, shipyard and services. PT Citra Tubindo, Tbk is one of the manufacturing companies located in the metal sub sector and other types listed on the Stock Exchange which are affected by the economic development in Batam City, which caused the decline in financial performance and financial distress. This study aims to predict bankruptcy in PT Citra Tubindo company, using the Altman Z-Score method. This method uses financial statements to be analyzed using variables from Z-Score. The analytical technique used is the prediction model of bankruptcy Altman Z-score. Using five variables representing liquidity ratios (X1), profitability (X2) and (X3), activity (X4) and (X5). With scoring criteria Z Score> 2.99 is categorized as a healthy company. 1.81 <Z-Score <2.99 is categorized as vulnerable so the possibility of rescue and possibly bankrupt is as great as it depends on the decision of the company management policy as the decision maker. Z-Score <1.81 is categorized as a company that has a very large financial difficulties and high risk so that the possibility of bankruptcy is very large. The results showed that PT Citra Tubindo has Z-score value in 2016 potentially prone to bankruptcy. It means that it is difficult to decide whether the company will go bankrupt or not. While in 2015 and 2017 the company potentially bankrupt .PT Citra Tubindo, Tbk has an unfavorable financial performance and needs to make improvements by improving financial liquidity ratio, profitability and activity.